Comparative study of laparoscopic cholecystectomy with and without drains - D., Dharamdev; Mascarenhas, Rupa Merlyn; Bhandary, Anand (International Surgery Journal, 2021)
Background: Gallstones and cholecystitis are very common pathologies in surgical practice. Laparoscopic cholecystectomy (LC) is the preferred procedure to remove the gallbladder (GB) worldwide. The main objective of this study was to evaluate the merits and demerits of placing drain after LC and to find out the clinico-pathologic conditions in which the placement of drain was justifiable. Methods: 100 patients who underwent LC were divided into 2 groups, group A (patients with drain) and group B (patients without drain). Interventional type, single-blind study was done. Complete history, evaluation and relevant data of both groups were done and analysed using descriptive statistics and Chi square test. Results: In group A, 44% were males and 56% females whereas in group B, 42% were males and 58% were females. There was a statistically significant difference (p value<0.05) between 2 groups in Visual analog scale (VAS) grading. Wound infection was seen in 14% in group A and 02% in group B; mean hospital stay in group A was 8.38±1.86 days and in group B was 4.68±1.25 days. Nausea and vomiting were noted in 46% among group A and 04 % among group B. Conclusions: Placement of drain after LC has nothing to offer, in contrast, it was associated with more pain. It would be reasonable to leave a drain if there was worry about an unsolved or potential bile leak only.